2016
DOI: 10.1097/mou.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Cancer immunotherapy

Abstract: The ICIs have changed the way urologic malignancies are treated and newer combinations are likely to alter the therapeutic landscape in these diseases dramatically in the coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Clinical applications of immunotherapy include boosting the immune response with exogenous cytokines, administering vaccines for tumor-associated antigens, and activating targeted antibodies on the surface proteins of immune checkpoint molecules [18]. In normal physiology, immune checkpoints suppress the adaptive immune response to prevent incorrect or prolonged T-cell activation [25]. In this process, antigen presentation to the T cells by antigen-presenting cells (APCs) is the key component.…”
Section: The Rationale For Immunotherapy In Urothelial Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical applications of immunotherapy include boosting the immune response with exogenous cytokines, administering vaccines for tumor-associated antigens, and activating targeted antibodies on the surface proteins of immune checkpoint molecules [18]. In normal physiology, immune checkpoints suppress the adaptive immune response to prevent incorrect or prolonged T-cell activation [25]. In this process, antigen presentation to the T cells by antigen-presenting cells (APCs) is the key component.…”
Section: The Rationale For Immunotherapy In Urothelial Carcinomamentioning
confidence: 99%
“…The binding of CD28 proteins on T cells to the proteins on APCs causes T-cell proliferation. The T cell inhibition cascade is activated after cytotoxic T-lymphocyte associated antigen 4 (CTLA-4) is bound to its ligands (B7-1 or B7-2), or when programmed death 1 (PD-1) protein binds to its PD-L1 ligand on the surface of tumor cells or APCs [25]. Cancer cells may evade the anti-tumor immune response by exploiting these immune checkpoint pathways and inhibiting the host immune cell (IC) proliferation [26].…”
Section: The Rationale For Immunotherapy In Urothelial Carcinomamentioning
confidence: 99%
“…21F-(b)(1) uyarınca, SEC bir kişinin ödül alabilmeye hak kazanıp kazanamayacağına karar vermektedir 147 . Muhbir, SEC'nin kriterlerine göre ödül almaya hak kazanırsa, SEC tarafından uygulanacak parasal yaptırımların %10-%30'u arasında muhbire bir ödeme yapılmaktadır 148 .…”
Section: A Tesla Payları üZerinde Elon Musk Tarafından İşlenen Piyas...unclassified
“…58 Dendritic cells dysfunction is one of the major causations of BC, and the increase in the number and activity of mature DCs in tumor tissue by DC vaccine and other approaches can enhance the immune killing effect on tumor. 59 Wang et al indicated that B7-H1 silencing could enhance the antitumor effect of bladder cancer by antigen-expression DC, which provided a new strategy for BC immunotherapy. 60 Aside from BCG and DC vaccines, there are numerous reports on the use of immunotoxin coupled mAb, IFN-α, IL-2, etc.…”
Section: Immunotherapy and Biomarkers For Curative Effect Predictionmentioning
confidence: 99%